Microplastic Contamination and Exposure in Gastropods: A Literature Review - Nadia Dwihajra Musrin; Ramadhan Tosepu; Ranno Marlany Rachman; Asnia Zainuddin; Surya Cipta Ramadhan Kete; Ridwan Adi Surya (Journal of Epidemiology and Health Science, 2025)
Background: Microplastic contamination in waterways continues to increase and has been detected in various gastropod species. Living on the seabed makes gastropods susceptible to accumulating microplastics, which can potentially impact the health of organisms and become a route of exposure for humans through the consumption of seafood. Objective: Reviewing the literature on microplastic contamination levels in gastropods, the shapes and types of polymers accumulated, and their implications for human health. Method: The Systematic Literature Review (SLR) followed the PRISMA guidelines, using articles from Scopus, ScienceDirect, PubMed, and Google Scholar (2014–2024) with criteria for empirical studies of microplastics in gastropods and related marine biota. Results: Gastropods in various locations were found to contain microplastics, predominantly in the form of fibers, fragments, and films, with PE and PP as the main polymers. The reported sizes varied, ranging from 100 nm–10 µm in Bellamya aeruginosa to 0.250–5 mm in Cerithidea obtusa. This exposure has the potential to affect the health of organisms and increase the risk of transfer of hazardous chemicals to humans. Conclusion: Gastropods serve as bioindicators of microplastic pollution and a route of exposure for humans. Controlling plastic pollution, monitoring marine products, educating the public, and harmonizing analytical methods are key to reducing ecological and health risks.